Modified membrane to improve vanadium redox flow battery performance - Goh, Julian Yu Han (Nanyang Technological University, 2022)
The Vanadium Redox Flow Battery (VRFB) has been garnering more usage and recognition due to its extensive capabilities in large scale energy storage applications. One of the vital components of the VRFB is the membrane, that determines the performance and price competitiveness of the battery. The membrane separates the positive and negative half-cells, thus preventing the cross mixing of the different electrolytes, while facilitating the ion transport during the charging and discharging process. Properties that are desirable in a VRFB membrane include high ion selectivity, high ion conductivity, low water uptake and swelling ratio, good chemical stability, good mechanical strength and durability and low cost. The membrane contributes to a significant portion of the cost in the VRFB system. This report will thus focus on the different types of membranes used in the VRFB systems, their classifications, properties, preparation methods and applications. The various types of membranes are compared, and the future developments of Cation exchange membranes and Anion exchange membranes are further investigated. Lastly, the future research direction in the development of a commercial membrane that displays a high performance while maintaining a low cost is identified.